Inverse Trig Integral

Calculus Level 3

0 1 arcsin ( x ) arccos ( x ) d x \int_0^1\arcsin(x)\arccos(x)\ dx

If the solution to the integral above can be expressed in the form a + b π a+b\pi , where a a and b b are rational, find a b \dfrac ab .


The answer is -4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Naren Bhandari
Jan 24, 2019

we make substitution of sin 1 x = u \sin^{-1} x =u which gives us d x = cos u d u \,dx = \cos u\,du . Thus we have I = 0 1 2 π u cos u cos 1 ( cos ( π 2 u ) ) d u = π 2 0 1 2 π u cos u d u 0 1 2 π u 2 cos u d u I=\int_{0}^{\frac{1}{2}\pi}u\cos u \cos^{-1} \left(\cos \left(\frac{\pi}{2}-u\right)\right)\,du =\dfrac{\pi}{2}\int_{0}^{\frac{1}{2}\pi}u \cos u \,du-\int_{0}^{\frac{1}{2}\pi} u^2\cos u\,du Using IBP we evalute the integrals as π 2 0 1 2 π u cos u d u = π 2 4 π 2 \dfrac{\pi}{2}\int_{0}^{\frac{1}{2}\pi}u \cos u \,du =\dfrac{\pi^2}{4}-\dfrac{\pi}{2} and using IBP twice 0 1 2 π u 2 cos u d u = π 2 4 2 \int_{0}^{\frac{1}{2}\pi} u^2\cos u\,du = \dfrac{\pi^2}{4} -2 which gives us I = ( π 2 4 π 2 ) ( π 2 4 2 ) = 2 π 2 I= \left(\dfrac{\pi^2}{4} -\dfrac{\pi}{2}\right) -\left(\dfrac{\pi^2}{4} -2 \right)=2-\dfrac{\pi}{2} thus a b = 4 \dfrac{a}{b} =-4

Here is the generalized problem.

Chew-Seong Cheong
Jan 25, 2019

I = 0 1 sin 1 x cos 1 x d x Note that cos 1 x = π 2 sin 1 x = π 2 0 1 sin 1 x d x 0 1 ( sin 1 x ) 2 d x By integration by parts \begin{aligned} I & = \int_0^1 \sin^{-1} x \cos^{-1} x \ dx & \small \color{#3D99F6} \text{Note that } \cos^{-1} x = \frac \pi 2 - \sin^{-1} x \\ & = \frac \pi 2 \int_0^1 \sin^{-1} x \ dx - \int_0^1 \left(\sin^{-1} x\right)^2 dx & \small \color{#3D99F6} \text{By integration by parts} \end{aligned}

= π x sin 1 x 2 0 1 0 1 π x 2 1 x 2 d x x ( sin 1 x ) 2 0 1 + 0 1 2 x sin 1 x 1 x 2 d x = π 2 4 + π 1 x 2 2 0 1 π 2 4 2 1 x 2 sin 1 x 0 1 + 2 0 1 d x = π 2 0 + 2 = 2 π 2 \begin{aligned} \ \ & = \frac {\pi x \sin^{-1} x}2 \bigg|_0^1 - \int_0^1 \frac {\pi x}{2\sqrt{1-x^2}} dx - x (\sin^{-1} x)^2 \bigg|_0^1 + \int_0^1 \frac {2x\sin^{-1}x}{\sqrt{1-x^2}} dx \\ & = \frac {\pi^2}4 + \frac {\pi \sqrt{1-x^2}}2 \bigg|_0^1 - \frac {\pi^2}4 - 2 \sqrt{1-x^2} \sin^{-1} x\bigg|_0^1 + 2 \int_0^1 \ dx \\ & = - \frac \pi 2 - 0 + 2 = 2 - \frac \pi 2 \end{aligned}

Therefore, a b = 2 1 2 = 4 \dfrac ab = \dfrac 2{-\frac 12} = \boxed{-4} .

Mark Hennings
Jan 23, 2019

We have, using the substitution y = cos 2 θ y = \cos2\theta , 0 1 sin 1 x d x = 0 1 0 x d y 1 y 2 d x = 0 1 y 1 d x d y 1 y 2 = 0 1 1 y 1 y 2 d y = 0 1 1 y 1 + y d y = 0 1 4 π tan θ × 2 sin 2 θ d θ = 4 0 1 4 π sin 2 θ d θ = [ 2 θ sin 2 θ ] 0 1 4 π = 1 2 π 1 \begin{aligned} \int_0^1 \sin^{-1}x\,dx & = \; \int_0^1 \int_0^x \frac{dy}{\sqrt{1-y^2}}\,dx \; = \; \int_0^1 \int_y^1\,dx \frac{dy}{\sqrt{1-y^2}} \; = \; \int_0^1 \frac{1-y}{\sqrt{1-y^2}}\,dy \; = \; \int_0^1 \sqrt{\frac{1-y}{1+y}}\,dy \\ & = \; \int_0^{\frac14\pi} \tan\theta \times 2\sin2\theta\,d\theta \;= \; 4\int_0^{\frac14\pi}\sin^2\theta\,d\theta \; = \; \Big[2\theta - \sin2\theta\Big]_0^{\frac14\pi} \; = \; \tfrac12\pi - 1 \end{aligned} and 0 1 ( sin 1 x ) 2 d x = [ x ( sin 1 x ) 2 ] 0 1 2 0 1 x sin 1 x 1 x 2 d x = 1 4 π 2 2 0 1 x 1 x 2 0 x d y 1 y 2 d x = 1 4 π 2 2 0 1 1 1 y 2 y 1 x d x 1 x 2 d y = 1 4 π 2 2 0 1 1 1 y 2 [ 1 x 2 ] y 1 d y = 1 4 π 2 2 0 1 d y = 1 4 π 2 2 \begin{aligned} \int_0^1 (\sin^{-1}x)^2\,dx & = \; \Big[x(\sin^{-1}x)^2\Big]_0^1 - 2\int_0^1 \frac{x\sin^{-1}x}{\sqrt{1-x^2}}\,dx \; = \; \tfrac14\pi^2 - 2\int_0^1 \frac{x}{\sqrt{1-x^2}}\int_0^x \frac{dy}{\sqrt{1-y^2}}\,dx \\ & = \; \tfrac14\pi^2 - 2\int_0^1 \frac{1}{\sqrt{1-y^2}}\int_y^1 \frac{x\,dx}{\sqrt{1-x^2}}\,dy \; = \; \tfrac14\pi^2 - 2\int_0^1 \frac{1}{\sqrt{1-y^2}}\Big[-\sqrt{1-x^2}\Big]_y^1\,dy \\ & = \; \tfrac14\pi^2 - 2\int_0^1\,dy \; = \; \tfrac14\pi^2 - 2 \end{aligned} so that 0 1 sin 1 x cos 1 x d x = 0 1 sin 1 x ( 1 2 π sin 1 x ) d x = 1 2 π ( 1 2 π 1 ) ( 1 4 π 2 2 ) = 2 1 2 π \int_0^1 \sin^{-1}x\,\cos^{-1}x\,dx \; = \; \int_0^1 \sin^{-1}x\left(\tfrac12\pi - \sin^{-1}x\right)\,dx \; = \; \tfrac12\pi\left(\tfrac12\pi - 1\right) - \left(\tfrac14\pi^2 - 2\right) \; = \; 2 - \tfrac12\pi making a = 2 a = 2 , b = 1 2 b = -\tfrac12 , and hence a b = 4 \tfrac{a}{b} = \boxed{-4} .

@Mark Hennings Sir, an easier approach in my opinion would be substituting arcsin(x) as t and then proceeding in a single integral and a simple Integration by Parts.........

Aaghaz Mahajan - 2 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...